2019
DOI: 10.1186/s12995-018-0222-9
|View full text |Cite
|
Sign up to set email alerts
|

Stress, health, noise exposures, and injuries among electronic waste recycling workers in Ghana

Abstract: BackgroundElectronic waste (e-waste) recycling workers in low and middle-income countries have the potential for occupational injuries due to the nature of their work at informal e-waste sites. However, limited research exists on stress, noise, occupational injuries, and health risks associated with this work environment. This study evaluated injury experience, noise exposures, and stress risk factors among e-waste workers at the large recycling site in the Agbogbloshie market, Accra, Ghana.MethodsParticipants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 42 publications
2
47
0
Order By: Relevance
“…These results can be integrated into the existing literature. Burns et al and Yu et al assessed injuries among the e-waste workers at Agbogbloshie, although Burns et al focused on the role of noise exposure and Yu et al predominantly explored the health knowledge of e-waste workers [16,17,19]. Ohajinwa et al observed that cuts on hands/fingers among e-waste workers were the most common injuries [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results can be integrated into the existing literature. Burns et al and Yu et al assessed injuries among the e-waste workers at Agbogbloshie, although Burns et al focused on the role of noise exposure and Yu et al predominantly explored the health knowledge of e-waste workers [16,17,19]. Ohajinwa et al observed that cuts on hands/fingers among e-waste workers were the most common injuries [18].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the assessment of health effects associated with e-waste processing in Agbogbloshie, only two studies addressed the occupation related stress-strain axis. Burns et al interviewed workers and found an association between noise exposure and the elevation in average heart rate as well as the number of injuries [16,17]. In Nigeria, the other important West African UEEE hub, only one study investigated a high rate of injuries among workers in the e-waste sector [18].…”
Section: Introductionmentioning
confidence: 99%
“…These chemicals have been detected in humans and in increasing concentrations in various environmental matrixes, including air, water, soil, sediment, animals, and foods in all regions of the world [15]. Evidence of effects of exposure to informal e -waste recycling include injuries [8,16], infection of wounds, skin and eye injuries and irritations, respiratory problems [17,18], and noise pollution, occupational stress, among others [19]. There is also evidence on harmful effects of long-term exposure of humans and wildlife, including effects on fetal/child development, impacts on thyroid and neurologic functions, immunotoxicity, reproductive toxicity, and endocrine disruption with endpoints related to induction of cancer [17]: See Table 1 for more information on health effects due to exposure to organic and metal contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it has created an avenue for the use of uncontrolled and crude methods to recover valuable materials from e-waste. The health and environmental effects of such informal crude recycling activities are not necessarily taken into consideration by the workers [44][45][46].…”
Section: Nigeria and Ghanamentioning
confidence: 99%